THE IMPACT OF BUSINESS MODEL INNOVATION AND DIGITAL LEADERSHIP ON BUSINESS PERFORMANCE: ANALYZING THE MODERATING ROLE OF EMPLOYEE TENURE - Muhamad Fazrur Rizal; Popy Rufaidah (Fakultas Ekonomi dan Bisnis, Universitas Airlangga, 2026)
Introduction: This study aims to examine the impact of business model innovation and digital leadership on business performance, with employee tenure as a moderating factor. Methods: A quantitative approach was used, involving a survey distributed to middle and upper manager at PT Telkom Indonesia. Data analysis was conducted using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. Results: The results show that both BMI and DL positively and significantly enhance business performance, with BMI exerting the strongest direct effect. Importantly, the findings reveal that employee tenure negatively moderates the relationship between BMI and performance, indicating that long-established routines and cognitive inertia among long-tenured employees can constrain the performance gains from business model reconfiguration. In contrast, employee tenure does not significantly alter the impact of digital leadership, suggesting that effective digital leadership operates broadly across tenure groups. Conclusion and suggestion: The study extends dynamic capabilities theory by showing that employee tenure shapes how effectively business model innovation creates value. It also refines digital leadership theory by demonstrating that leadership impacts performance across tenure groups. For emerging economies, the findings emphasize the need for adaptive human capital strategies alongside digital investment.